The global burden of childhood diarrhea and its epidemiological characteristics from 1990 to 2021 - Zhu, Hai-Yan; Xu, Fan; Zhao, Wen-Zhuo; Wang, Hai-Xiao; Wang, Hong-Gang (Frontiers in Pediatrics, 2025)
IntroductionDiarrhea diseases remains a major contributor to global mortality and morbidity in children. This study aims to provide an updated assessment of rates in diarrhoea prevalence, incidence, mortality, and disability-adjusted life-years (DALYs) from 1990–2021, specifically focusing on including prevalence investigation alongside other measures. The analysis is stratified by sex, age, and socio-demographic index (SDI) at global, regional, and national levels.MethodsData for this study was obtained from the 2021 Global Burden of Diseases, Injuries, and Risk Factors Study (GBD). Children aged 0–14 years with diarrhea were included in the analysis. The analyses were disaggregated by gender, 3 age categories, 21 GBD regions, 204 nations/territories, and 5 SDI quintiles. Incidence, all-cause mortality, cause-specific mortality, disability-adjusted life years (DALYs), and the corresponding estimated annual percent changes (EAPCs) were investigated.ResultsIn 2021, the global burden of diarrhea diseases remained substantial, with a total of 2,432,874,591 cases with an ASPR of 1,252.09 cases per 100,000 individuals (95% UI: 1,032.41–1,474.93). The ASIR was 83,866.84 per 100,000 people (95% UI: 66,140.64–101,854.13), while the ASDR was 18.6 per 100,000 persons (95% UI: 13.99–24.79). Additionally, the age-standardized DALY rate was 1,784.28 per 100,000 individuals (95%UI: 1,361.38–2,320.22). Regionally, areas with high-middle SDI exhibited the greatest ASPR, ASIR, ASDR, and age-standardized DALY rates, whereas high SDI regions had the lowest rates. The ASPR is mostly concentrated in children aged 10–14 years old, among which the ASPR of children under 5 years old has the most significant decline, from 3,138.81 per 100,000 people (95% UI: 2,749.19–3,557.51) in 1,990–885.07 per 100,000 people (95% UI: 755.93–1,029.39), a decrease of 71%. Geospatially, South Asia had the highest ASPR and the highest ASIR. The most pronounced increase was noted in the high-income Asia-Pacific region, which is the only area exhibiting growth, with an EAPC of 1.46 (95% CI: 1.11–1.82). Interestingly, between 1990 and 2021, the ASDR in Western Europe displayed the most pronounced rise, with an EAPC of 0.81, whereas the steepest decline was observed in East Asia. The greatest ASDR and age-standardized DALY rates were observed in the western region of sub-Saharan Africa, West Africa and Central Africa. Among countries, Madagascar had both the highest ASIR and ASDR. Furthermore, African countries exhibited the highest age-standardized DALY rate. Globally, unsafe water sources remained the primary risk factor for childhood diarrhea mortality and disability-adjusted life years (DALYs) from 1990–2021. While predominant in all Sociodemographic Index (SDI) regions except high-SDI areas, high-SDI regions reported non-exclusive breastfeeding and childhood wasting as leading mortality risk factors. Unsafe water sources are expected to persist as the principal contributor in the future.DiscussionThe burden of childhood diarrhea diseases globally has been decreasing but remains a substantial contributor to DALYs. Low-middle SDI regions show persistently high age-standardized rates, with South Asia bearing the highest burden. Our study clarifies the global and regional epidemiology of childhood diarrheal diseases and identifies unsafe water sources as the predominant risk factor. These findings highlight the need for region-specific water safety initiatives in high-burden areas and are vital for shaping public health strategies and policy decisions for prevention.